Stress reactivity in war-exposed young children with and without posttraumatic stress disorder: Relations to maternal stress hormones, parenting, and child emotionality and regulation. (8th November 2013) - Feldman, Ruth; Vengrober, Adva; Eidelman-Rothman, Moranne; Zagoory-Sharon, Orna
Abstract: The current study examined biomarkers of stress in war-exposed young children and addressed maternal and child factors that may correlate with children's stress response. Participants were 232 Israeli children aged 1.5–5 years, including 148 children exposed to continuous war. Similarly, 56 were diagnosed with posttraumatic stress disorder (PTSD) and 92 were defined as exposed-no-PTSD. Child cortisol (CT) and salivary alpha amylase (sAA), biomarkers of the hypothalamic–pituitary–adrenal and sympathetic–adrenal–medullary arms of the stress response, were measured at baseline, following challenge, and at recovery. Maternal CT and sAA, PTSD symptoms, and reciprocal parenting, and child negative emotionality and regulatory strategies were assessed. Differences between war-exposed children and controls emerged, but these were related to child PTSD status. Children with PTSD exhibited consistently low CT and sAA, exposed-no-PTSD displayed consistently high CT and sAA, and controls showed increase in CT following challenge and decrease at recovery and low sAA. Exposed children showed higher negative emotionality; however, whereas exposed-no-PTSD children employed comfort-seeking strategies, children with PTSD used withdrawal. Predictors of child CT included maternal CT, PTSD symptoms, low reciprocity, and negative emotionality. Findings suggest that high physiological arousal combined with approach strategies may be associated with greater resilience in the context of early trauma.